Disaster Research "Methics": Ethical and Methodological Considerations of Researching Disaster-Affected Populations. (July 2020) - Van Brown, Bethany L.
How we do research directly affects what we know about the subject matter under study. While the study of disaster events continues to grow, rigorous inquiry on disaster research methodology is limited because it is confounded by the disruption a disaster presents. Yet it is precisely at that point that special methodological problems emerge. The methodological—and inherently ethical—challenges disaster researchers face became apparent to me during my own fieldwork on domestic violence organizations and their recovery trajectory following Hurricanes Katrina and Rita in 2005. In this article, I explore methodological and ethical issues that lay beneath "studying" people in the wake of disaster events and argue that ethical concerns should have the same, if not greater, primacy as methods; a dual consideration I refer to as "methics." My findings support this argument and add to the growing chorus advocating for a paradigm shift in disaster research methods.